Triphosphine ligands: coordination chemistry and recent catalytic applications - Phanopoulos,A; Long,NJ; Miller,PW (Springer, 2016)
Phosphines are a long established class of ligand that are known to form a vast array of transition metal complexes. They behave as neutral electron pair donors, or Lewis bases, that alter the solubility and stereoelectronic properties of the metal centre. A key motivation for their continued development is for homogeneous catalysis. For over five decades, transition metal–phosphine complexes have been used for catalytic reactions, mainly exploiting monodentate or bidentate phosphine ligands. Multidentate phosphines by comparison have received much less attention in part because they tend to form more stable complexes with a saturated coordination environment around the metal centre. Recent developments in the areas of catalytic reduction of carboxylic acid derivatives using molecular hydrogen and in the field of biomass up-conversion have exploited catalysts based on tridentate phosphines. This chapter highlights the use of these multidentate phosphines for synthesis of coordination complexes and discusses some of their recent applications in homogeneous catalysis.